ATM pathway activation limits R-loop-associated genomic instability in Werner syndrome cells. Issue 7 (18th January 2019) - Marabitti, Veronica; Lillo, Giorgia; Malacaria, Eva; Palermo, Valentina; Sanchez, Massimo; Pichierri, Pietro; Franchitto, Annapaola
Abstract: Werner syndrome (WS) is a cancer-prone disease caused by deficiency of Werner protein (WRN). WRN maintains genome integrity by promoting replication-fork stability after various forms of replication stress. Under mild replication stress, WS cells show impaired ATR-mediated CHK1 activation. However, it remains unclear if WS cells elicit other repair pathway. We demonstrate that loss of WRN leads to enhanced ATM phosphorylation upon prolonged exposure to aphidicolin, a specific inhibitor of DNA polymerases, resulting in CHK1 activation. Moreover, we find that loss of WRN sensitises cells to replication-transcription collisions and promotes accumulation of R-loops, which undergo XPG-dependent cleavage responsible for ATM signalling activation. Importantly, we observe that ATM pathway limits chromosomal instability in WS cells. Finally, we prove that, in WS cells, genomic instability enhanced upon chemical inhibition of ATM kinase activity is counteracted by direct or indirect suppression of R-loop formation or by XPG abrogation. Together, these findings suggest a potential role of WRN as regulator of R-loop-associated genomic instability, strengthening the notion that conflicts between replication and transcription can affect DNA replication, leading to human disease and cancer.